2008
DOI: 10.1002/chem.200701747
|View full text |Cite
|
Sign up to set email alerts
|

Towards the Rational Design of MRI Contrast Agents: Electron Spin Relaxation Is Largely Unaffected by the Coordination Geometry of Gadolinium(III)–DOTA‐Type Complexes

Abstract: Electron-spin relaxation is one of the determining factors in the efficacy of MRI contrast agents. Of all the parameters involved in determining relaxivity it remains the least well understood, particularly as it relates to the structure of the complex. One of the reasons for the poor understanding of electronspin relaxation is that it is closely related to the ligand-field parameters of the Gd 3+ ion that forms the basis of MRI contrast agents and these complexes generally exhibit a structural isomerism that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
47
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(49 citation statements)
references
References 74 publications
2
47
0
Order By: Relevance
“…The apparent maxima of the spectrum of both complexes is at approximately 30800 cm -1 (325 nm), which is consistent with the singlet-state energies of other pyridine-containing complexes. [29] The addition of Zn [30] For instance, it has been shown that the nature and polarizability of the group occupying a position on or close to the principal axis of the complex affects the relative intensity of the 5 D 0 Ǟ 7 F 2 transition. [31] The more polarizable the axial donor atom is, the greater the relative The hydration states of the EuL1 and EuL2 complexes were studied by comparison of their luminescence lifetimes in H 2 O and D 2 O.…”
Section: Absorption and Emission Electronic Spectroscopymentioning
confidence: 99%
“…The apparent maxima of the spectrum of both complexes is at approximately 30800 cm -1 (325 nm), which is consistent with the singlet-state energies of other pyridine-containing complexes. [29] The addition of Zn [30] For instance, it has been shown that the nature and polarizability of the group occupying a position on or close to the principal axis of the complex affects the relative intensity of the 5 D 0 Ǟ 7 F 2 transition. [31] The more polarizable the axial donor atom is, the greater the relative The hydration states of the EuL1 and EuL2 complexes were studied by comparison of their luminescence lifetimes in H 2 O and D 2 O.…”
Section: Absorption and Emission Electronic Spectroscopymentioning
confidence: 99%
“…MRI is a noninvasive imaging technique used for diagnosis of diseases [1][2][3][4][5][6][7][8][9][10][11][12][13]. When a biological sample is placed under an MRI scanner, the magnetic field perturbs the equilibrium spin state of the sample [2,4,10,13].…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15][16][17][18][19][20] For instance, SPION nanoclusters have been used as a negative contrast agent in liver and heart imaging, 21 and SPION-folate-poly(ethylene glycol) has been used for lung cancer imaging. 22 The microbubbles used in this investigation represent a novel microdevice consisting of poly(vinyl alcohol) (PVA) containing SPION in between the shells.…”
mentioning
confidence: 99%